2004
DOI: 10.1111/j.1745-9133.2004.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Poverty, State Capital, and Recidivism Among Women Offenders*

Abstract: Research Summary: This research investigates the effects of poverty and state capital (i.e., state‐sponsored support) on recidivism among women offenders. We seek also to determine whether criticisms directed at actuarial risk tools, such as the failure to take into account gender‐related factors (e.g., poverty status), have merit. A community corrections sample of 134 female felony offenders from one county in the State of Oregon and in the cities of Minneapolis and St. Paul, Minnesota is used to examine self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
166
2
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(181 citation statements)
references
References 44 publications
6
166
2
7
Order By: Relevance
“…While empirical evidence suggests that adult females would benefit from a gender-specific risk assessment tool (Holtfreter & Cupp, 2007;Holtfreter & Morash, 2003;Holtfreter, Reisig, & Morash, 2004;Van Voorhis, Wright, Salisbury, & Bauman, 2010), the topic has not been as extensively studied for juveniles, and findings are mixed. Some studies have found that gender-neutral tools do not accurately predict risks for juvenile females, and suggest that they may benefit from a gender-specific risk assessment tool (Baird et al, 2013;Schmidt, Campbell & Houlding, 2011).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…While empirical evidence suggests that adult females would benefit from a gender-specific risk assessment tool (Holtfreter & Cupp, 2007;Holtfreter & Morash, 2003;Holtfreter, Reisig, & Morash, 2004;Van Voorhis, Wright, Salisbury, & Bauman, 2010), the topic has not been as extensively studied for juveniles, and findings are mixed. Some studies have found that gender-neutral tools do not accurately predict risks for juvenile females, and suggest that they may benefit from a gender-specific risk assessment tool (Baird et al, 2013;Schmidt, Campbell & Houlding, 2011).…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, a more likely explanation is that gender differences in offending are more pronounced in adult offenders than their juvenile counterparts. Since there have been more significant findings on gender differences with studies using the adult versions of the LSI (Holtfreter & Cupp, 2007;Holtfreter & Morash, 2003;Reisig, Holtfreter, & Morash, 2006;Holtfreter, Reisig, & Morash, 2004) than in youth versions, it could be that gendered experiences in adulthood (i.e.. violent victimization and substance abuse) may lead to differences in offending, rather than assuming that these experiences occur in childhood or adolescence.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Similarly, measures of the quality and nature of women's social relationships were not available. Although this problem is common in this type of research (Holtfreter et al, 2004), mixed-method research may best describe the intra-individual changes in recidivism while capturing more subtle elements of social relationships and offender change.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of childcare, discrimination, and conflict with employers have been identified as central to women's reduced employment rate upon release (Golden, 2005;Harm & Phillips, 2001;Richie, 2001;Schram, KoonsWitt, Williams, & McShane, 2006). Moreover, poor inner-city women often travel in isolated, small social circles that preclude them from developing strong social networks that may provide opportunities for employment and social and economic advancement prior to and post-release (Reisig, Holtfreter, & Morash, 2002); thus, making reentry more challenging and recidivism more likely (Holtfreter, Reisig, & Morash, 2004). Although there is evidence that attachment to work can facilitate desistance from criminal behavior among women (Simons, Stewart, Gordon, Conger, & Elder, 2002;Uggen & Kruttschnitt, 1998), these findings have not been replicated with a sample of female parolees.…”
Section: Gendered Pathwaysmentioning
confidence: 99%
“…Female prisoners have also largely been characterized as socially and economically marginalized offenders who demonstrate unique needs pertaining to their histories of victimization or abuse, substance use, mental health problems, and traumatic relationships (Bloom et al, 2003(Bloom et al, , 2004Heilbrun et al, 2008;Holtfreter, Reisig, & Morash, 2004;Koons-Witt & Schram, 2003;McDaniels-Wilson & Belknap, 2008;Reisig, Holtfreter, & Morash, 2002;Reisig et al, 2006). Women often have low levels of education and poor job skills that tend to keep them employed at low-paying and low-skilled jobs (e.g., as clerks).…”
Section: Women's Needsmentioning
confidence: 99%